The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1021/ja9614326
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Isotope Effects in H2O−D2O Mixtures (Proton Inventories) on Serine-Protease-Catalyzed Hydrolysis Reactions. Influence of Oxyanion Hole Interactions and Medium Effects

Abstract: Rates of hydrolysis of succinyl-Ala-Ala-Pro-Phe-p-nitroanilide catalyzed by subtilisin and its N155G mutant were measured in H2O, D2O, and “HDO” (1:1 H2O:D2O). The solvent isotope effects (proton inventories) determined by these data showed no differences between the wild-type and mutant enzymes, despite the fact that the mutation removes a hydrogen-bonding interaction in the oxyanion hole of the enzyme worth two orders of magnitude in reaction rate. This suggests that curvature previously observed (ref ) in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 24 publications
3
17
0
Order By: Relevance
“…www.chembiochem.org system, of a multiplicity of small isotope effects [28] adding up to give the relatively large cumulative number.…”
mentioning
confidence: 99%
“…www.chembiochem.org system, of a multiplicity of small isotope effects [28] adding up to give the relatively large cumulative number.…”
mentioning
confidence: 99%
“…8,9 Chang et al reported that medium effect is also important in that regard. 10 This study in particular investigates the plausibility of explicit solvent molecules other than water molecules proximal to the transition states in acting as the oxyanion-hole environment.…”
mentioning
confidence: 99%
“…The question of which of these steps is rate limiting does not influence the isotope-effect arguments. Kresge immediately pointed out (5) the ambiguity of this interpretation, and later expanded on the point with the inclusion of experimental measurements on an enzymecatalyzed reaction and on host-guest complexation (6,7). A linear dependence such as we observed (eq.…”
Section: Introductionmentioning
confidence: 81%